Exploration of the Implementation of Standard Operating Procedures (SOPs) in the Production Process at J&C Cookies Bandung: Eksplorasi Penerapan Standard Operating Procedure (SOP) dalam Proses Produksi di J&C Cookies Bandung - Ocha Dwi Riestu; Tsaniyah Jumhuriyah; Nayla Rizky Dwi Firnanda; Satrio Sudarso (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Standard Operating Procedures (SOPs) serve as critical operational guidelines for ensuring product quality, operational efficiency, and stringent quality control in the food manufacturing sector. Specific Background J&C Cookies Bandung, a prominent Indonesian bakery enterprise, implements multi-stage production processes for roombutter cookies and holiday hampers distributed locally and internationally. Knowledge Gap However, empirical research exploring real-time SOP implementation, procedural compliance, and quality control mechanisms across each specific stage of cookie manufacturing remains scarce. Aims This study investigates the systematic implementation of SOPs across production stages at J&C Cookies Bandung, evaluating their role in operational effectiveness and identifying execution challenges. Results Utilizing a qualitative descriptive approach via direct field observation, semi-structured interviews, and documentation, findings reveal that SOPs are systematically enforced from employee hygiene preparation to dough mixing, molding, dual-energy baking (170–180°C), and packaging. Novelty This research highlights how strict moisture control, roombutter formulation, and shape-based product differentiation (such as crescent-shaped nastar) simultaneously secure a 1-year preservative-free shelf life and enhanced market competitiveness. Implications Operational adherence to SOPs substantially minimizes contamination risks, standardizes food safety compliance, and elevates consumer trust in medium-scale food processing industries. Keywords: Standard Operating Procedure (SOP), Production Process, Food Industry, Product Quality, Hygiene, J&C Cookies Bandung Key Findings Highlights Standard operating procedures at J&C Cookies Bandung are systematically implemented at every production stage, from employee preparation to product packaging. The product achieves a shelf life of up to one year without preservatives by keeping moisture levels close to zero percent during baking. Product differentiation is successfully established through shape innovations, such as crescent-shaped nastar, and moisture-controlled packaging designs.